Genomics4RD: An integrated platform to share Canadian deep‐phenotype and multiomic data for international rare disease gene discovery. Issue 6 (9th March 2022) - Driver, Hannah G.; Hartley, Taila; Price, E. Magda; Turinsky, Andrei L.; Buske, Orion J.; Osmond, Matthew; Ramani, Arun K.; Kirby, Emily; Kernohan, Kristin D.; Couse, Madeline; Elrick, Hillary; Lu, Kevin; et al.
Abstract: Despite recent progress in the understanding of the genetic etiologies of rare diseases (RDs), a significant number remain intractable to diagnostic and discovery efforts. Broad data collection and sharing of information among RD researchers is therefore critical. In 2018, the Care4Rare Canada Consortium launched the project C4R‐SOLVE, a subaim of which was to collect, harmonize, and share both retrospective and prospective Canadian clinical and multiomic data. Here, we introduce Genomics4RD, an integrated web‐accessible platform to share Canadian phenotypic and multiomic data between researchers, both within Canada and internationally, for the purpose of discovering the mechanisms that cause RDs. Genomics4RD has been designed to standardize data collection and processing, and to help users systematically collect, prioritize, and visualize participant information. Data storage, authorization, and access procedures have been developed in collaboration with policy experts and stakeholders to ensure the trusted and secure access of data by external researchers. The breadth and standardization of data offered by Genomics4RD allows researchers to compare candidate disease genes and variants between participants (i.e., matchmaking) for discovery purposes, while facilitating the development of computational approaches for multiomic data analyses and enabling clinical translation efforts for new genetic technologies in the future. Abstract : Here we present Genomics4RD, an integrated and internationally accessible web platform, to share, store, and visualize phenotypic and multiomic data from rare disease patients across Canada. Genomics4RD is connected to several other rare disease databases for the purposes of matchmaking and disease‐gene discovery.